La nature, le rôle et l'influence de la doctrine universitaire en droit administratif québécois - Macdonald, Roderick (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
In view of the increasingly divergent tendencies in legal scholarship, many authors are reconsidering whether « la doctrine » can really serve as a formal source of law. Since university professors are primarly responsible for producing this scholarly commentary, at least in the field of administrative law, it is worth asking two related questions : first, does university scholarship in law have a specific purpose or logic ? and second, does the nature of administrative law require that this scholarship have a particular direction ? In this essay, both questions are answered in the affirmative : University legal scholarship has a synthetic function not shared by ordinary legal writing, and given the case law foundations of the administrative law, this scholarship must also reveal the underlying conceptual structure of the subject.